2015
DOI: 10.1111/jpm.12208
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nurses can increase capability and capacity in primary care by educating practice nurses: an evaluation of an education programme in England

Abstract: Most people with a mental health problem in England are cared for by clinicians in primary care who may have had little or no training in this area. Our aim was to develop an accessible education programme which was appropriate to the learning needs of this workforce. A survey of the mental health and well-being training needs and preferred learning methods of practice nurses was undertaken, then a programme of education was developed by a primary care mental health expert. Teaching was delivered by mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…While the interface between primary care and specialist mental health services is important, given the need to strengthen primary care mental health services, this review is focussed solely on aspects of primary care service delivery. Given that 55% of American physicians treat psychological illnesses internally (13) and 90% of individuals in England receive mental health treatment solely in primary care without seeing a specialist (14), service delivery in primary care is vital to managing mental health within the community (9).…”
Section: Introductionmentioning
confidence: 99%
“…While the interface between primary care and specialist mental health services is important, given the need to strengthen primary care mental health services, this review is focussed solely on aspects of primary care service delivery. Given that 55% of American physicians treat psychological illnesses internally (13) and 90% of individuals in England receive mental health treatment solely in primary care without seeing a specialist (14), service delivery in primary care is vital to managing mental health within the community (9).…”
Section: Introductionmentioning
confidence: 99%
“…One example is the practice nurse project, which was led by one of us (S.H.) and funded by Health Education North Central East London (HENCEL) (Hardy 2015b). This 10-module training developed for practice nurses covers most areas recommended by HEE and was successfully delivered by mental health nurses working in the practice nurses’ localities.…”
Section: Improving Parity Of Esteemmentioning
confidence: 99%
“…There have been three published evaluations of primary care nurse training to carry out physical health screening in people with SMI in England. They have all shown an increase in participants’ perceived knowledge and skills, and positivity about taking on the role of looking after people with SMI (Hardy , Hardy & Huber , Hardy & Kingsnorth ). Regrettably, these three training programmes have all been short‐term projects based in particular geographical areas.…”
Section: Nurse Trainingmentioning
confidence: 99%
“…One method of achieving this is for mental health nurses to offer education to the primary care nurses. A project where mental health nurses were trained to become primary care nurse educators has been shown to provide an opportunity to start building communication processes between primary and secondary care (Hardy & Kingsnorth ). Additionally, mental health nurses reported that being a trainer did not take them away from clinical practice for long periods and improved both their clinical practice and that of the nurses they taught.…”
Section: Communication Between Primary and Secondary Carementioning
confidence: 99%